Preparation and antitumor activity of selenium-modified glucomannan oligosaccharides. (February 2020) - Li, Kuikui; Qi, Huan; Liu, Qishun; Li, Tang; Chen, Wei; Li, Shuguang; Piao, Hai-long; Yin, Heng
Graphical abstract: Highlights: A glucanase with high activity and substrate specificity for KGM was identified. High selenium content selenium-modified glucomannan oligosaccharides was prepared. Selenium-modified glucomannan oligosaccharides have high antitumor activity. Antitumor activity induced apoptosis through the mitochondrial pathway. Abstract: Konjac glucomannan is safely and widely used in the functional food industry. Compared with glucomannan, glucomannan oligosaccharides have higher water solubility making them easier to absorb and utilize. These oligosaccharides are also associated with many biological activities. A novel glucomannan hydrolase Pp GluA with high activity and substrate specificity which releases a series of konjac glucomannan oligosaccharides having DP 2–9 is described here. Selenium is one of the essential trace elements for humans. The selenium-modified glucomannan oligosaccharides were prepared by the sodium selenite-nitric acid method for the first time. Antitumor activity studies demonstrated that selenium-modified glucomannan oligosaccharides had better activity than inorganic sodium selenite and glucomannan oligosaccharides and inhibited tumor by inducing apoptosis through the mitochondrial pathway. This study suggests that selenium-modified glucomannan oligosaccharides may be have potential as a new functional food for inhibition of tumors.